Postmortem examination of human fetuses: comparison of two‐dimensional ultrasound with invasive autopsy. (7th January 2019) - Kang, X.; Shelmerdine, S. C.; Hurtado, I.; Bevilacqua, E.; Hutchinson, C.; Mandalia, U.; Segers, V.; Cos Sanchez, T.; Cannie, M. M.; Carlin, A.; Sebire, N. J.; Arthurs, O. J.; et al.
ABSTRACT: Objective: To assess the diagnostic accuracy of postmortem ultrasound performed by operators blinded to prenatal findings and to invasive autopsy results in fetuses at different gestational ages and to investigate the effect of various parameters on its diagnostic success. Methods: We performed postmortem two‐dimensional ultrasound examination, blinded to clinical details, on 163 fetuses at 13–42 weeks' gestation. Logistic regression analysis was used to investigate the effect of: (i) gestational age at postmortem ultrasound, (ii) presence of maceration and (iii) mode of death, on whether the exam succeeded or failed to reach a diagnosis. In 123 cases in which invasive autopsy was available, the diagnostic accuracy of ultrasound in detecting major organ abnormalities was evaluated, using invasive autopsy as the gold standard. Results: For the fetal brain, postmortem ultrasound exam was non‐diagnostic in significantly more fetuses with maceration (39.5%; 17/43) vs those without maceration (20.0%; 24/120) ( P  = 0.013). For the fetal thorax, the exam was non‐diagnostic in 34.1% (15/44) of fetuses < 20 weeks of gestation and in 10.9% (13/119) of fetuses ≥ 20 weeks ( P  < 0.001). For the heart and abdominal organs, there was no association between non‐diagnostic postmortem ultrasound and the variables tested. For fetuses < 20 weeks, specificity of postmortem ultrasound examination was 83.3% for detection of anomalies of the brain, 68.6% for the thorax and 77.4% for the heart. For fetuses ≥ 20 weeks, sensitivity and specificity were, respectively, 61.9% and 74.2% for detection of anomalies of the brain, 29.5% and 87.0% for the thorax and 65.0% and 83.1% for the heart. For the fetal abdominal organs, sensitivity was 60.7% and specificity 75.8%, and postmortem ultrasound was particularly useful for detection of abnormalities of the kidneys, irrespective of gestational age. Conclusion: Although maceration may lead to failure of postmortem ultrasound examination in some cases, this technique achieves diagnostically acceptable levels of accuracy for fetal brain and abdominal organs, compared with conventional autopsy. It may therefore play a role as a first‐line examination before other virtual autopsy techniques are indicated. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.